Analisis Faktor-Faktor yang Mempengaruhi Deindustrialisasi di Indonesia - Pasaribu, Cory; Sirojuzilam, Sirojuzilam; Syafii, Muhammad (Universitas Batanghari Jambi, 2024)
This research aims to analyze the effect of decreasing the proportion of GRDP in the industrial/manufacturing sector which is influenced by PMDN, PMA, income per capita and analyzing the moderation of the number of working people on the influence of PMDN on the decline in the proportion of GRDP in the industrial/manufacturing sector, analyzing the moderation of the number of working people on the influence of PMA on the decline in the proportion of GRDP in the industrial/manufacturing sector, analyzing the moderation in the number of working people on the influence of per capita income on the decline in the proportion of GRDP in the industrial/manufacturing sector in 34 provinces in Indonesia in the period 2002-2021 using the Fixed approach Effect Model (FEM) as a panel data regression model. In this research, the moderating test will be carried out using Moderated Regression Analysis (MRA). Partial test results show that PMDN has a positive and significant effect, PMA has a negative and significant effect, Income per capita has a negative and significant effect on the decline in the proportion of GRDP in the industrial/manufacturing sector, The number of employed people moderates the influence of PMDN, The number of employed population moderates the influence of PMA, and The number of working people does not moderate the effect of per capita income on the decline in the proportion of GRDP in the manufacturing/industrial sector.